Cybernetics and Automation Control Theory Methods in Intelligent Algorithms Proceedings of 8th Computer Science On-line Conference 2019, Vol. 3 - Silhavy, Radek (Advances in Intelligent Systems and Computing, 2019)
This book discusses novel intelligent-system algorithms and methods in cybernetics, presenting new approaches in the field of cybernetics and automation control theory. It constitutes the proceedings of the Cybernetics and Automation Control Theory Methods in Intelligent Algorithms Section of the 8th Computer Science On-line Conference 2019 (CSOC 2019), held on-line in April 2019. .